Highest Defoliation Tolerance in Amaranthus cruentus Plants at Panicle Development Is Associated With Sugar Starvation Responses - Cisneros-Hernández, Ismael; Vargas-Ortiz, Erandi; Sánchez-Martínez, Estefany S.; Martínez-Gallardo, Norma; Soto González, Daniela; Délano-Frier, John Paul (Frontiers in Plant Science, 2021)
Defoliation tolerance (DT) in Amaranthus cruentus is known to reach its apex at the panicle emergence (PE) phase and to decline to minimal levels at flowering (FL). In this study, defoliation-induced changes were recorded in the content of non-structural carbohydrates and raffinose family oligosaccharides (RFOs), and in the expression and/or activity of sugar starvation response-associated genes in plants defoliated at different vegetative and reproductive stages. This strategy identified sugar-starvation-related factors that explained the opposite DT observed at these key developmental stages. Peak DT at PE was associated with increased cytosolic invertase (CI) activity in all organs and with the extensive induction of various class II trehalose-phosphate synthase (TPS) genes. Contrariwise, least DT at FL coincided with a sharp depletion of starch reserves and with sucrose (Suc) accumulation, in leaves and stems, the latter of which was consistent with very low levels of CI and vacuolar invertase activities that were not further modified by defoliation. Increased Suc suggested growth-inhibiting conditions associated with altered cytosolic Suc to hexose ratios in plants defoliated at FL. Augmented cell wall invertase activity in leaves and roots, probably acting in a regulatory rather than hydrolytic role, was also associated with minimal DT observed at FL. The widespread contrast in gene expression patterns in panicles also matched the opposite DT observed at PE and FL. These results reinforce the concept that a localized sugar starvation response caused by C partitioning is crucial for DT in grain amaranth.